Making Use of Difference: Diversity, Debate, and Decision Comprehensiveness in Top Management Teams - Simons, Tony; Pelled, Lisa Hope; Smith, Ken (Academy of Management Journal, 1999)
This study examined how top management team diversity variables and debate interacted to influence two measures of company financial performance. Further, it assessed the degree to which decision comprehensiveness mediated those interaction effects. Multi-informant data from the top management teams of 57 manufacturing companies revealed that more job-related types of diversity interacted with debate to influence financial performance, but a less job-related type (age diversity) did not. Decision comprehensiveness partially mediated those effects.